Explicit or Implicit Grammar Instruction in EFL? Teachers’ and Learners’ Perceptions - Balderas Ruiz, Luis Antonio; Vela Gámez, Martha Alicia (Verbum et Lingua: Didáctica, lengua y cultura, 2024)
This study investigated the perceptions that teachers and learners of English as a Foreign Language (EFL) have regarding explicit and implicit grammar instruction (GI). Both types of GI are described as taking place in meaning-based communicative classrooms. They differ in that explicit GI involves conscious awareness of the form of the language learners need to know to understand grammar in context. However, implicit instruction occurs during communicative activities without any previous explanation of the language's form. The research problem concerns a grammar gap related to EFL teachers´ and learners´ perceptions of English grammar instruction not being considered in EFL classrooms. A quantitative method structured this study, which focused on 45 teachers and 355 students randomly selected from a language center at a university in northern Mexico. Previously designed questionnaires (Valeo & Spada, 2016) were translated, adapted, and used for data collection. Factor analysis was conducted throughout the research, and the results support the validity of the questionnaires.